Pengaruh Social Media Marketing Dan Kualitas Produk Terhadap Loyalitas Pelanggan Pada PT. Bank Perkreditan Rakyat Hasamitra: indonesia - Verawaty, Verawaty; Muchsiddin, Murdin; Ceskakusumadewi, Ceskakusumadewi; Salam, Karta Negara; Azis, Murwinda (Movere Journal, 2023)
In social media marketing, product quality is needed to increase loyalty, product quality is the ability of goods and services to meet customer needs (Jay and Barry, 2014: 244). Quality can be fulfilled when the company can provide products in accordance with what customers expect, product quality is the overall characteristic of a product that can meet customer needs according to what customers absorb. Consumers will feel satisfied because of the experience in purchasing a product used. Product quality has an important role in meeting customer satisfaction in shaping customers to be worthy of the products offered by the company. The customer's decision is described after comparing what is expected with what the company offers. The purpose of this study is to determine the influence of social media marketing and product quality on the loyalty of PT. Bank Perkreditan Rakyat Hasamitra. The analysis method used is quantitative and qualitative descriptive analysis methods, namely by multiple linear regression analysis, data processing using SPSS. Based on the results of regression testing that has been carried out shows that simultaneously and continuously between social media marketing variables have a positive and significant effect on product quality, product quality variables have a positive and significant effect on customer loyalty. While social media marketing variables affect product quality variables and customer loyalty positively and significantly